1999
DOI: 10.1152/ajpheart.1999.276.3.h1058
|View full text |Cite
|
Sign up to set email alerts
|

Flow regulation of ecNOS and Cu/Zn SOD mRNA expression in porcine coronary arterioles

Abstract: The purpose of this study was to test the hypothesis that increased flow through coronary arterioles increases endothelial cell nitric oxide synthase (ecNOS) and Cu/Zn superoxide dismutase (SOD) mRNA expression. Single porcine coronary arterioles (ID 100–160 μm; pressurized) were cannulated, perfused, and exposed to intraluminal flow sufficient to produce maximal flow-induced dilation of coronary arterioles (high flow; 7.52 ± 0.22 μl/min), low flow (0.84 ± 0.05 μl/min), or no flow for 2 or 4 h. Mean shear stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 23 publications
4
82
0
1
Order By: Relevance
“…Shear stress has also been shown to increase pro-oxidants, including NOS formation of NO and SOD (Malek et al 1995;Uematsu et al 1995;Corson et al 1996;Dimmeler et al 1999;Woodman et al 1999 under H 2 O 2 -induced oxidative stress under both shear and static conditions. The overall goal of these studies is to provide a possible model for disease development within the vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shear stress has also been shown to increase pro-oxidants, including NOS formation of NO and SOD (Malek et al 1995;Uematsu et al 1995;Corson et al 1996;Dimmeler et al 1999;Woodman et al 1999 under H 2 O 2 -induced oxidative stress under both shear and static conditions. The overall goal of these studies is to provide a possible model for disease development within the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endothelial nitric oxide synthase (NOS) can produce large amounts of O 2 .-when the enzyme becomes uncoupled from its normal substrates (Milstien et al 1999;Witteveen et al 1999;Vasquez-Vivar et al 2002;Zou et al 2002;Landmesser et al 2003 (Beckman et al 1990;Pryor et al 1995), although this has not been demonstrated experimentally. Finally, endothelial cells in vivo are exposed to shear stress, which modulates many key aspects of endothelial metabolism and function, including NO release (Griffith 2002), NOS expression (Dimmeler et al 1999;Davis et al 2004), copper/zinc superoxide dismutase expression (Dimmeler et al 1999;Woodman et al 1999), and the expression of other endothelial cell genes (Malek et al 1995 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During exercise, blood flow increases to provide muscle with an adequate supply of oxygen and nutrients. It is well documented that flow/shear stress is an important signal regulating eNOS expression in blood vessels (19,27). Consequently, age-associated reductions in physical activity and associated increases in blood flow may remove an important signal for the maintenance of eNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for decreased SOD-1 protein expression may involve age-associated reductions in resting blood flow and associated shear stress. Similar to eNOS, shear stress is a primary signal regulating SOD-1 expression in cultured endothelial cells (12) and in intact arteries (27). In addition, decreased soleus muscle blood flow, induced by hindlimb unweighting, is associated with reductions in SOD-1 expression and ACh-induced dilation in SFA (28).…”
Section: Discussionmentioning
confidence: 99%